STUDI TENTANG MONUMEN SITI MANGGOPOH DI KECAMATAN LUBUK BASUNG - FEBRIYANTO, Dra. Lisa Widiarti, M.Sn, Drs. Ir. Heldi, M.Si (Serupa The Journal of Art Education, 2015)
The purposes of the research are: (1) to describe the history of SitiManggapoh statue (2) to describefactors influencing the shape formation of Siti Manggapoh statue. This research is conducted by using qualitative method with descriptive approach. The data of this research are oral data from interviewand the a written source from the library as the secunder data.The data of this research were collected from observation, interview,documentation and bibliography. The results of this research are as follows: (1) the building of Siti Manggopoh statue was tied with the history of Manggopoh society struggling against the Dutch colonization; (2) The physical shape of the statue comprises of the base cornerstone, the base figure, and female statue’s figure. The techniques employed in the building of the statue arepelastering and carving. The process of the building started from designing, assembling, to finishing.Kata Kunci:Monument, Siti Manggopoh, Lubuk Basung